Penguatan Kapasitas Aparatur Pemerintah Desa - Henri Prianto Sinurat; Rati Sumanti (Puslatbang KHAN, 2016)
Policy to build Indonesia through village was realized with enactment of Law No. 6 of 2014 concerning the village. The village was positioned by the Law as a base of human resource, human resource and local wisdom so that the state is obliged to empower village as the center of development in order to improve the welfare of its people. Furthermore, the village head and the village community would be given opportunities to play a role as the subject of development. The village should be able to plan and implement their own development according to the needs and priorities of the community. To keep the condition balance, it is a must to strengthen the capacity of village government apparatus. The village requires adequate and professional apparatus resources to be subject of development which is capable to play strategic role to make a developed, independent and prosperous country. This paper shows that the development in the village suffered several problems including a weak system of planning at the village level, insufficient village heads competency, management of services to the community as well as the financial management of villages that have not been effective. All of these problems is basically a problem derived from the weak of apparatus resources ability in the village. To overcome the condition, there are at least (4) four agenda in strengthening the capacity of the village government apparatus that needs to be done and is owned by each village apparatus; the ability of government management, the ability of village development planning, the ability of village financial management and the ability in drafting village regulation. The implementation of the agenda requires leadership commitment to do the reinforcement. By strengthening the capacity of the village government apparatus, not only in terms of the theory but also in practice, the village government will be able to perform its functions in implementing development in the region.